(3aJM GdeJYGd aj eOM GdfYGds - (3GdebQj , CMeO Hf eMeO Hf CMeO Hf jMji GdJdeSGfj, CHh GdYHGS,J (B1041 (3g` s ((3SdjeGf Hf YHOGdMb s)
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ Edi QMeI QHg CMeO Hf eMeO GdebQi fMeOc Gddge Cf LYdJfG cef CeI NjQ ef eTi HGdfYdjf hSeG Ydi Cgd GdCQV hGdSeGA GdCYdjf s
(3BNQgG (B:s
(3hcGf GdaQGZ ef JMQjQg HThGd ef YGe KdGKjf hCda EdG ehGVY MQQJ hCdMbJ HYO Pdc hcdg HGdbGgQI GdeMQhSI s
(3hajgG HYV QShe JhVjMjI ddfYds
(3haj BNQ GdfSNI HYV JbQjXGJ ddcJGHs
(3hjSei CjVG GdfaMGJ GdYfHQjI aj fYGd NjQ GdHQjI hbO PcQgeG HQhcdef Ydi CfgeG cJGHGfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs